A reflection of Social Forestry in 2019: Towards inclusive and collaborative government approaches - Suharjito, Didik; Wulandari, Christine (Forest and Society, 2019)
In this policy forum, we seek to engage in a discussion related to the acceleration of social forestry approaches, foremost led by the Ministry of Environment and Forestry (MOEF), and supported by civil society actors. This article thus points to three key areas of reflection being raised among forums at different governing scales at the end of 2018. The first is a reflection of the national level issues discussed in a forum convened by MOEF in partnership with the media organization Tempo Magazine. The second is part of a reflection on a forum conducted by the Lampung province, which was convened by a coalition of NGOs. Finally, the third forum for reflection involved a public consultation about a study on the impacts of social forestry in South Sulawesi. These three forums highlighted that there is a sharp increase in formal social forestry designations by bureaucratically requiring regions to submit proposals, which are then followed up by verification of sites. This has resulted in a large increase in the number of social forestry permits and has also had the consequence of opening up bureaucratic access (in this case by MOEF) to civil society organizations in more inclusive and collaborative ways. However, on the other hand, we also found that amidst these discussions, there was also a strong element of recentralization emerging in the forestry sector related to permits, in which decision-making powers were being redirected to the central government. Another finding that emerged involves the weakening of capacity among communities themselves to benefit from social forestry designations. Therefore, although there are indications of positive engagement by government towards the principles of collaboration, concerns also emerge about the ways community engagement is unfolding. Overall, this highlights important considerations for improving social forestry policy and implementation for the future.